Bio-Dynamics and Life Cycle of Shrimp (Penaeus Semisulcatus De Haan), in Bushehr Coastal Waters of the Persian Gulf - Niamaimandi, Nassir (2006)
Shrimp fisheries in the Persian Gulf have a long history. The trawl fishery for penaeid prawn developed along the mid-northern coasts of the Persian Gulf (Bushehr waters) beginning in 1960. From 1998 to 2004 shrimp landings have fluctuated between 480t and 2700t per year. The major species of penaeid prawn, in terms of catch (>80%) and economic importance, in the Persian Gulf (including Bushehr waters) is Penaeus semisulcatus, commonly known as the green tiger prawn. More than 2000 vessels and 33000 fishermen from the Bushehr study area have participated in the shrimp fishery each season (August-September) over the last decade. In the Arabian side of the Persian Gulf, P. semisulcatus has been now become the most important single component species. Despite of commercial importance, there has been very little published research in the biology this species. In the study area, Bushehr waters, shrimp fishery is only controlled during open season. Because of lack of any data, there is no any prohibition and restricted areas in the nursery and spawning grounds and also the fluctuations of shrimp resources are unknown. The present study was carried out in Bushehr coastal waters during 2003-2005 and describes the bio-dynamics and life history of P. semisulcatus. Monthly sampling of shrimp was collected by R/V Lavar II for 15 months from January 2003 to March 2004 from 50 fixed stations. Carapace length (CL) frequency was used to estimate growth, mortality and exploitation rates for males and females using FiSAT statistical analyses software. The Von Bertalanffy growth parameters were estimated as K = 1.6 Year-1 and 2.2 Year-1 and L¥ = 38 mm and 50.4 mm for males and females, respectively. Estimated annual mortality rates for males were Z = 6.4, F= 4.3, and M = 2.11. While females were Z = 8.2, F = 5.8, and M = 2.41. Exploitation rates for males and females were E = 0.67 and E = 0.70, respectively. Relatively high values of total mortality and exploitation rates were obtained, suggesting this species is overexploited. The maximum ages calculated were 20 months for males and 15 months for females.